The effect of product market focus on the relationship between board quality and earnings management - Mitra Pourmohammadian; Sajad Bahri (New Applied Studies in Management, Economics & Accounting, 2020)
The purpose of this study is to investigate the effect of product market focus on the relationship between board quality and earnings management among companies listed on the Tehran Stock Exchange. To achieve this goal, the modified Jones model was used in calculating earnings management and a total of 8 mechanisms were used to calculate the quality of the board of directors; Modified Lerner and Herfindahl-Hirschman indices were also used to calculate product market focus. The statistical sample includes 82 companies during the period of 2009 to 2018. Hypothesis testing was performed using linear regression with Eviews software. The results showed that there is a significant and posiitve relationship between board quality and earnings management, while product market focus does not moderate the relationship between board quality and earnings management.